(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Students in the colleges usually deploy the sites of social networking. The aims for which the sites of the social networking are used, in addition to their impacts on social interaction, learning, and relations with friends and family, were explored in this work. At Al Qasim Green University’s Physical Development and Sport Science Collage, a cross-sectional study was done among 155 students aged between 18 and 30. The data was gathered via a questionnaire. According to the findings, all students utilized social networking apps. Just 2% of them utilized social media to further their education. While 48% of them used such platforms for chatting with others. In addition, 75% of them have been addicted to social media. Furthermore, 89% said social media had a detrimental impact on their studies, 80% said that they have been more drawn to the social media compared to the academic pursuit, and 85% had stated that their free time is spent on the social media platforms. The most widely used applications (depending on usage): Telegram was sued by 26% of students, Facebook was used by 40%, Instagram by 22%, YouTube by 6%, LinkedIn and Twitter by 2%. Furthermore, only 2% of students have accounts on all social networking sites identified in the work. About half of the students (52%) have at least three social media accounts, succeeded by three accounts (22%), two accounts (15%), and one account (11%). Lastly, 47% of them said they spent at least three hours every day on social media. Almost all participants have stated they have utilized the sites of the social networking for the non-academic purposes for a long time. Those behaviors could result in diverting the students’ attentions away from their study, had negative impacts on their social connections and academic performances, and result in a physical inactivity and sedentary lifestyle, making them essential to mental health issues and non-communicable diseases.